Ensuring better access to education for the disabled - Abdul Razak, Dzulkifli (New Straits Times Press (M) Bhd., 2019)
In Malaysia, some 488,948 OKUs were registered with the Jabatan Kebajikan Masyarakat as at October last year. But the number of them gaining an education is relatively small. For example, the International Islamic University Malaysia, which launched its own Disability Inclusion Policy in November last year which is in tandem with the university’s raison d’etre, has some 150 and 10 OKU students and staff respectively. This is due to a number of barriers such as attitude, financial, physical, communication and organisational. The latest being migrational in nature. Indeed, in 2016 the UN estimated that less than half of the world’s six million refugee children were in school. Lesser still in university.